Crisis сommunication in social work during the war - Plakhova, Olena (SOCIOPROSTIR: the Interdisciplinary Online Collection of Scientific Works on Sociology and Social Work, 2022)
<span dir="ltr" style="left: calc(var(–scale-factor)*92.06px); top: calc(var(–scale-factor)*211.10px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.971784);" role="presentation">The article analyzes the concepts of crisis and crisis communication in social work. The author notes the <span dir="ltr" style="left: calc(var(–scale-factor)*56.64px); top: calc(var(–scale-factor)*222.53px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.960406);" role="presentation">relevance of the need for the scientific development of algorithms and programs of crisis communications in social <span dir="ltr" style="left: calc(var(–scale-factor)*56.64px); top: calc(var(–scale-factor)*234.05px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.959963);" role="presentation">work during the war. Crisis communication in social work is defined as the establishment of sustainable interaction <span dir="ltr" style="left: calc(var(–scale-factor)*56.64px); top: calc(var(–scale-factor)*245.57px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.915311);" role="presentation">between local governments, civil society institutions, social institutions, churches, business representatives, and contact <span dir="ltr" style="left: calc(var(–scale-factor)*56.64px); top: calc(var(–scale-factor)*257.09px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.915015);" role="presentation">audiences (community residents, internally displaced persons, families of fallen soldiers, and other categories of victims <span dir="ltr" style="left: calc(var(–scale-factor)*56.64px); top: calc(var(–scale-factor)*268.61px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.916807);" role="presentation">of warfare) about existing problems and needs, their prompt resolution by all participants of the interaction. <span dir="ltr" style="left: calc(var(–scale-factor)*92.06px); top: calc(var(–scale-factor)*280.01px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.976565);" role="presentation">The following key properties of crisis communication in social work are identified by the author: flexibility <span dir="ltr" style="left: calc(var(–scale-factor)*56.64px); top: calc(var(–scale-factor)*291.53px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.98437);" role="presentation">and adaptability of methods of interaction between subjects; strengthening the informal means of reception and <span dir="ltr" style="left: calc(var(–scale-factor)*56.64px); top: calc(var(–scale-factor)*303.05px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.978506);" role="presentation">transmission of information; reduction of centralism in the communication process; promptness of the situational <span dir="ltr" style="left: calc(var(–scale-factor)*56.64px); top: calc(var(–scale-factor)*314.57px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.892405);" role="presentation">response to emerging problems. <span dir="ltr" style="left: calc(var(–scale-factor)*92.06px); top: calc(var(–scale-factor)*326.09px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.929185);" role="presentation">Crisis communication in social work is a sequence of actions that form a сеrtain communication strategy. The <span dir="ltr" style="left: calc(var(–scale-factor)*56.64px); top: calc(var(–scale-factor)*337.61px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.92232);" role="presentation">article determines the requirements for the development of a communication strategy during martial law in Ukraine and <span dir="ltr" style="left: calc(var(–scale-factor)*56.64px); top: calc(var(–scale-factor)*349.01px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.932825);" role="presentation">measures for its implementation, namely: identification of all possible contact audiences expecting <span dir="ltr" style="left: calc(var(–scale-factor)*465.41px); top: calc(var(–scale-factor)*349.01px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.942047);" role="presentation">information about <span dir="ltr" style="left: calc(var(–scale-factor)*56.64px); top: calc(var(–scale-factor)*360.53px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.958556);" role="presentation">further actions; reporting only verified and confirmed information; establishment of channels for receiving feedback <span dir="ltr" style="left: calc(var(–scale-factor)*56.64px); top: calc(var(–scale-factor)*372.07px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.917797);" role="presentation">from the contact audiences, as well as systematicity of two-way interaction of the subjects; assessment of the strengths <span dir="ltr" style="left: calc(var(–scale-factor)*56.64px); top: calc(var(–scale-factor)*383.59px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.941795);" role="presentation">and weaknesses of the communication activities carried out in order to avoid mistakes in crisis communication in the <span dir="ltr" style="left: calc(var(–scale-factor)*56.64px); top: calc(var(–scale-factor)*395.11px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.955503);" role="presentation">future. The author emphasizes that the crisis contains both potential threats and the danger of loss, as well as new <span dir="ltr" style="left: calc(var(–scale-factor)*56.64px); top: calc(var(–scale-factor)*406.63px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.96861);" role="presentation">renewal and transformation opportunities for society, creating new modern approaches to interaction after a crisis <span dir="ltr" style="left: calc(var(–scale-factor)*56.64px); top: calc(var(–scale-factor)*418.03px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.921988);" role="presentation">period. Crisis phenomena in society will contribute to the emergence of new or modification of existing social practices, <span dir="ltr" style="left: calc(var(–scale-factor)*56.64px); top: calc(var(–scale-factor)*429.55px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.974767);" role="presentation">and cause a reaction to them from the public. As a result, new behavioral and communication practices and new <span dir="ltr" style="left: calc(var(–scale-factor)*56.64px); top: calc(var(–scale-factor)*441.07px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.923816);" role="presentation">subjects of interaction will emerge.